2023
DOI: 10.1371/journal.pone.0290497
|View full text |Cite
|
Sign up to set email alerts
|

A 3D printed electronic wearable device to generate vertical, horizontal and phono-articulatory jaw movement parameters: A concept implementation

Taseef Hasan Farook,
Saif Ahmed,
Md Shoriful Islam Talukder
et al.

Abstract: Purpose The current research aimed to develop a concept open-source 3D printable, electronic wearable head gear to record jaw movement parameters. Materials & methods A 3D printed wearable device was designed and manufactured then fitted with open-source sensors to record vertical, horizontal and phono-articulatory jaw motions. Mean deviation and relative error were measured invitro. The device was implemented on two volunteers for the parameters of maximum anterior protrusion (MAP), maximum lateral excu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In the current research landscape, several gaps have been identified: Despite the widespread application of data normalisation and synthetic signal processing in various medical signal-based datasets, the normalisation of EMG signals from masticatory muscles for broad applicability and correlation with similar image datasets from different facilities, devices and varying timeframes remains unexplored [ 22 ]. The development of a image-to-signal conversion system is necessary for mandibular EMG, but it must ensure that the converted signal features are classifiable through clustering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current research landscape, several gaps have been identified: Despite the widespread application of data normalisation and synthetic signal processing in various medical signal-based datasets, the normalisation of EMG signals from masticatory muscles for broad applicability and correlation with similar image datasets from different facilities, devices and varying timeframes remains unexplored [ 22 ]. The development of a image-to-signal conversion system is necessary for mandibular EMG, but it must ensure that the converted signal features are classifiable through clustering.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread application of data normalisation and synthetic signal processing in various medical signal-based datasets, the normalisation of EMG signals from masticatory muscles for broad applicability and correlation with similar image datasets from different facilities, devices and varying timeframes remains unexplored [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surface electromyography (BioEMG III, BioResearch Associates Inc., Brown Deer, WI, USA) to record masticatory muscle activity during mouth opening and closing. • Joint vibration analysis (JVA; BioResearch Associates Inc., Brown Deer, WI, USA) to evaluate TMJ function, producing mean vibration integrals and amplitudes above 300 Hz to assess joint complex quality during opening [16,21].…”
mentioning
confidence: 99%